The Existence of Translation Services at Language Centers in State Islamic Religious Universities - Karim, Haji Abdul; Baehaqi, Luqman (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2025)
This study aims to examine the existence of translation services at language centers in State Islamic Higher Education Institutions (PTKIN). It provides an in-depth analysis of the existence, transparency, and informational provisions of translation services currently in practice, as well as explores best practices that can be implemented by other PTKIN language centers in delivering translation services. A more in-depth study of the presence and function of translation services in PTKIN language centres can provide strategic recommendations for the development of these services. This research is a case study that employs a qualitative approach. The findings indicate that not all PTKIN institutions have integrated translation services within their language centres. Additionally, the principle of public information transparency, which should serve as the foundation for service transparency and accountability in language centres, has not yet been fully and evenly implemented. Nevertheless, some PTKIN language centres have demonstrated best practices in translation services, such as providing clear information on procedures and technical requirements on their websites, as well as utilizing information system technology or applications. The findings of this study and the best practices that already implemented in several PTKIN language centres can serve as a reference for the future development of translation services.